KALIMAT IMPERATIF DALAM NOVEL THE KILL ORDER KARYA JAMES DASHNER - KAREPOUWAN, VITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
This research attempts to identify , describe and analyze the imperative sentences in the novel The Kill Order written by James Dashner. Imperative sentence is the verb that is used to give command, warning, advice, instruction, and request. The verb is one of the four parts of moods that are subjunctive, indicative, and infinitive. The data are taken from the novel of James Dashner, The Kill Order. The indentified data are analyzed according to the concept of Aarts and Aarts on form and function of imperative sentences in communication. In analyzing the data the writer uses descriptive method. The problem of this research are focused on what are the forms and functions of imperative sentence found in the novel The Kill Order. The aims of the research are to find out the forms and function of imperative sentence in the novel The Kill Order by James Dashner. The result of this research shows that the function of these entire imperative sentences found in novel are command, wish, invitation and warning. Command is the most used function in the novel. Key word: Imperative Sentences, Syntactic Analysis, Novel The Kill Order